CARR, Willem Jacobus Petrus Inventory of documents - CARR, Willem Jacobus Petrus (ARCA, 2017)
Private papers of W.J.P. Carr, Head of the Native Affairs Department of the Johannesburg Municipality [1925-1969]
COVERAGE 1928-1972; 135 Files; 2,00 Metres. AUDIO CASSETTES IN PRIVATE COLLECTION = 1
Keywords: CARR, Willem Jacobus Petrus; Inventories; Municipal workers; Native Affairs Department